Allogeneic hematopoietic stem-cell transplantation for patients with Richter transformation: a retrospective study on behalf of the Chronic Malignancies Working Party of the EBMT - Guièze, Romain; Eikema, Diderik-Jan; Koster, Linda; Schetelig, Johannes; Sengeloev, Henrik; Passweg, Jakob R.; Finke, Jürgen; Arat, Mutlu; Broers, Annoek E. C.; Stölzel, Friedrich; Byrne, Jenny; Castilla-Llorente, Cristina; et al. (Bone marrow transplantation, 2024)
Management of Richter transformation (RT) is particularly challenging, with survival estimates <1 year. We report on outcomes of 66 RT patients undergoing allogeneic-HCT (allo-HCT) between 2008 and 2018 registered with the EBMT. Median age at allo-HCT was 56.2 years (interquartile range (IQR), 51.3-63.1). Median time from RT to allo-HCT was 6.9 months (IQR, 4.9-11) and 28 (42.4%) were in complete remission (CR). The majority underwent reduced intensity conditioning (66.2%) using peripheral blood derived stem cells. Eighteen (27.3%) patients had a matched sibling donor, 24 (36.4%) a matched unrelated donor and the remaining were mismatched. Median follow-up was 6.6 years; 1- and 3- year overall and progression free survival (PFS) (95% CI) was 65% (54-77) and 39% (27-51) and 53% (41-65) and 29% (18-40), respectively. Patients in CR at time of allo-HCT had significantly better 3-year PFS (39% vs. 21%, p = 0.032). Cumulative incidences of grade II-IV acute graft versus host disease (GVHD) at day +100 was 41% (95% CI 29-53) and chronic GVHD at 3 years was 53% (95% CI 41-65). High rates of non-relapse mortality (NRM) were observed; 38% (95% CI, 26-50) at 3 years. Although potentially curative, approaches to reduce considerable NRM and chronic GVHD rates are required.